A physical activity barriers questionnaire for youth with visual impairments - Armstrong, Ellen; Lieberman, Lauren; Prokešová, Eva; Martiin, Jeffrey (Acta Universitatis Carolinae. Kinanthropologica, 2018)
Background. In the current paper we examined the psychometric properties of the Physical Activity Barriers Questionnaire for children with Visual Impairments (PABQ-VI). We examined evidence for the ability of the PABQ-VI to produce scores considered to be valid and exhibit internal reliability. Methods. Forty one children living in the USA who were attending a residential sports camp participated in our research. Psychometric properties of the PABQ-VI were investigated using Pearson product-moment coefficients, Cronbach’s alpha and split-half reliability tests. Convergent validity was established by exploring correlations between the PABQ-VI, physical activity (PA) levels and participant’s self-efficacy for overcoming barriers. Results. Participants demonstrated low PA levels. Both PA participation and barrier PA self-efficacy scores were correlated with the PABQ-VI. The most physically active participants perceived fewer barriers and had stronger efficacy compared to participants who were less physically active. Conclusions. Overall, the PABQ-VI demonstrated preliminary evidence of convergent validity. Future researchers may consider reducing participant burden by reducing the scale length through eliminating the most poorly performing items and examining the three-factor structure using factor analysis.
Keywords: Humans; Leisure Activities; zrakově postižení; Motor Activity; pohybová aktivita; Sports for Persons with Disabilities; Surveys and Questionnaires; mužské pohlaví; sporty pro handicapované; Adolescent; průzkumy a dotazníky; volnočasové aktivity; Persons with Visual Disabilities; ženské pohlaví; lidé; mladiství; dítě; Child; Male; Female